대학 교양 글쓰기 교과에서 과정 중심의 동료 평가 모델 제안 및 사례 연구 - 백송이(Song Ee Baek); 정희현(Hee Hyun Jung) (교양교육연구, 2025)
본 연구는 대학 교양 글쓰기 교과에서 논증 기반 글쓰기의 이론적 지식과 실질적 적용 사이의 간극을 해소하기 위한 “과정 중심의 동료 평가 모델”을 제안한다. 대학 교양 글쓰기는 학생들의 비판적⋅논리적 사고력 함양을 목표로 하지만, 형식적 지식 전달만으로는 실질적인 정당화 능력을 키우기 어렵다는 문제가 있다. 본 연구는 동료 평가에 대한 기존의 연구들이 결과물 중심으로 수행되었다는 한계를 지적하고, 이를 보완하기 위한 방안을 “과정 중심 동료 평가 모델”이라는 이름으로 제시한다. 이 모델은 학습자들에게 결과물이 아닌 글쓰기 과정에 집중하고, 다른 사람들의 글을 평가하게 함으로써 자신의 글쓰기 선호를 드러내고, 그 선호에 대한 인식이 불명확함을 깨닫게 하며, 자신의 방식에 대해 정당화하는 과정에서 그것을 반성하도록 유도한다. 그리고 이를 적용한 S 대학 사례를 보고함으로써, 이 모델의 효용 및 개선점을 제시한다. 본 연구는 이러한 과정 중심의 동료 평가 모델이 기존의 교수자 평가중심 모델의 한계를 극복하고, 학생들의 비판적 사고력과 논증 능력 향상에 실질적으로 기여할 수 있음을 보여준다. This study proposes a “Process-Oriented Peer Review Model” to bridge the gap between theoretical knowledge and practical application of argument-based writing in university liberal arts writing courses. Although university writing education aims to cultivate students' critical and logical thinking skills, there is a limitation in developing substantial justification abilities through formal knowledge transfer alone. This research identifies the limitations of existing peer review studies that have primarily focused on final products, and presents an alternative approach called the ‘Process-Oriented Peer Review Model.’ This model encourages learners to focus on the writing process rather than the final product, and by evaluating others' writing, it helps them reveal their own writing preferences, recognize the ambiguity of these preferences, and reflect on their writing methods through the process of justification. By reporting a case study implemented at S University, this research presents both the effectiveness and areas for improvement of this model. This study demonstrates that the process-oriented peer review model can overcome the limitations of traditional instructor-centered evaluation models and substantially contribute to enhancing students' critical thinking and argumentation skills. KCI Citation Count: 0